2012
DOI: 10.1177/0300985812446148
|View full text |Cite
|
Sign up to set email alerts
|

Subcuticular Urate Accumulation in an American Lobster (Homarus americanus)

Abstract: An unusually ''lumpy'' lobster, Homarus americanus, was presented to the Atlantic Veterinary College Lobster Science Centre for evaluation. The lobster was weak with numerous pale, raised, and flat areas (diameter, 3-15 mm) on the exoskeleton, some of which were ulcerated. On postmortem examination, the pale areas corresponded to accumulations of viscous to free-flowing white material, which was found in only the subcuticular connective tissues. No internal organs were affected. Direct light examination of non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It can be concluded that crabs may convert excess ammonia (except for direct excretion of ammonia) in the body into trace amounts of uric acid via purine nucleotide metabolism and that the uric acid is mainly stored in muscles. A small amount of uric acid was also detected in other crustaceans, such as the kuruma shrimp (Lee and Chen 2003), Norway lobster (Bernasconi and Uglow 2011), and American lobster Homarus americanus (Battison 2013). It was reported that uric acid was usually stored in the epidermis and gut cells and was discharged through molting or degraded via the uricolytic pathway (Regnault 1987).…”
Section: Effects Of Ammonia-nitrogen Exposure On Synthesis Pathways O...mentioning
confidence: 99%
“…It can be concluded that crabs may convert excess ammonia (except for direct excretion of ammonia) in the body into trace amounts of uric acid via purine nucleotide metabolism and that the uric acid is mainly stored in muscles. A small amount of uric acid was also detected in other crustaceans, such as the kuruma shrimp (Lee and Chen 2003), Norway lobster (Bernasconi and Uglow 2011), and American lobster Homarus americanus (Battison 2013). It was reported that uric acid was usually stored in the epidermis and gut cells and was discharged through molting or degraded via the uricolytic pathway (Regnault 1987).…”
Section: Effects Of Ammonia-nitrogen Exposure On Synthesis Pathways O...mentioning
confidence: 99%
“…Only a handful of papers have described hemolymph constituents and their parameters under normal or varying conditions for lobsters (see references in Dove et al 2005b;Battison 2006;Lorenzon et al 2007), and basic hemolymph panels for constituents and enzymes are not optimized for lobsters (Basti et al 2010). Thus it is not surprising that only two other metabolic diseases have been described from the American lobster -molting death syndrome (Bowser and Rosemark 1981) and the abnormal deposition of urate crystals in the subcuticular tissues (Battison 2013) -both of which caused gross changes to the cuticle of affected animals.…”
Section: Calcinosismentioning
confidence: 99%
“…Understanding how Portunus trituberculatus transports ammonia is essential for discovering how the ammonia-rich benthic water of crab habitats affects larval development and adult emergence. There are at least four ammonia transportation and metabolic pathways in crustaceans: excess internal ammonia is probably converted to glutamine (Gln) by the coupling of glutamate dehydrogenase (GDH) and glutamine synthetase (GS) (Anderson et al, 2002); urea is generated via the ornithine-urea cycle (OUC) (Chen and Chen, 1997) to reduce ammonia toxicity; a small amount of uric acid has also been detected in crustaceans, such as Marsupenaeus japonicus (Lee and Chen, 2003), Nephrops norvegicusto (Bernasconi and Uglow, 2011) and Homarus americanus (Battison, 2013); and as a major ammonotelic animal, active branchial ammonia excretion mechanisms are present in crabs to prevent unfavorable passive influxes (Weihrauch, 1999). Ammonia makes up around 86% of the total excreted nitrogen in Carcinus maenas (Needham, 1957), and 95% in Palaemonetes varians (Snow and Williams, 1971) and Crangon crangon (Regnault, 1983).…”
Section: Introductionmentioning
confidence: 99%